The Assistance for Digitalisation of MSME Products in Bentakan Village, Baki Sub-district, Sukoharjo Regency, Central Java: Pendampingan Digitalisasi Produk Umkm Desa Bentakan Kecamatan Baki Kabupaten Sukoharjo, Jawa Tengah - Novita Anisa; Raharjo Sigit; Hanuring Ayu; Ariy Kaerudin; Firstnandiar Glica (Institute of Educational, Research, and Community Service, 2023)
This community service research aims to identify and analyse the barriers and problems faced by MSME players, especially in terms of product digitalisation, product photography, and online marketing. MSME players in Bentakan Village, Sukoharjo Regency, have been marketing their products directly and online, but face a number of problems. One of the main problems is a limited understanding of product digitisation, poor quality product photos, and difficulty attracting consumers optimally. The majority of MSME players do oral marketing of their products, selling only when there is an order, so their income is irregular and less than optimal. Although they can use simple equipment such as gadgets to take product photos, they do not know how to do it well. Similarly, they can edit photos with free apps on the Play Store, but limited education and age are obstacles. Most of the MSME players in Bentakan Village are housewives with an average age of 40 who are lagging behind in technological development. The Bentakan KKN 2023 team provided training in this regard, including photo-taking and editing techniques